Substatiation of quantitative criteria of structural parts and units manufacturability evaluation - Yarosh, Yaroslav; Tsyvenkova, Nataliya; Kukharets, Savelii; Нolubenko Anna; Los, Leonid (Technology audit and production reserves, 2017)
The object of research is assemblability and maintainability of structures. Criteria for assessing such important parameters of design manufacturability are an extremely complex problem in the design process. The result of the design should be the embodiment of the idea in the form of a product. Low manufacturability significantly complicates this process, or even makes it impossible. One of the most problematic places in determining the criteria for assemblability and maintainability of structures is that their list differs depending on the design. With the increase in the number of details in the design, the process of determining the criteria and their quantitative assessment are significantly more complicated. The formalization of the criteria for manufacturability makes it possible to reduce the optimization process to a single algorithm, which has a high degree of automation. The potential for implementing the theory in CAD systems has become the starting point for the research. The use of research results, namely the formulated theorems of assemblability and maintainability, allows to optimize the design and evaluate the results of optimization qualitatively and quantitatively. It is advisable to use the indicated results for structures, the production of which provides for seriality – mass production and large-scale production. Under such conditions, the economic effect of the optimization is most palpable. Another advantage of the study is the answer to the question – in which the greatest number of design elements can achieve maximum assemblability and maintainability? The formulated conclusions make changes in the design algorithm and program the level of its optimality already in the design. It is this approach that reduces the level of material costs already at the design stages, technological preparation of production, and, directly, in production. The actual result of applying the developed optimization technique is increasing the manufacturability of the investigated structures from 30 to 50 %. In comparison with the known analogs, a basis has been created for the establishment and complex analysis of the manufacturability criteria as a result of the interaction of assemblability and maintainability.